Dynamic evolutionary pattern of fractures in tectonically deformed coal-bearing assemblages during loading - Pengxiang ZHAO; Yingying LIU; Shugang LI; Yanqun LIU; Yunchuan LIU; Laolao WANG; Weidong LU (Meitian dizhi yu kantan)
ObjectiveThe formation and evolution of fractures in tectonically deformed coals (TDCs) exert a significant influence on the occurrence of dynamic hazards to TDC-bearding combinations under mining disturbance. However, the influence patterns remain unclear. MethodsUsing a NanoVoxel-3000 high-resolution inspection system for multiscale integrated geotechnical scanning and analysis, this study performed uniaxial compression and CT scanning experiments on TDC-bearing combination specimens. Moreover, this study reconstructed the mesoscopic geometric structures of the specimens using the Avizo software, obtaining three-dimensional visualization models of fractures inside the specimens. Results and Conclusions During loading of a specimen studied, fractures were generated in the TDC first and then propagated toward the upper and lower coals with primary textures, with the numbers of radial and longitudinal fractures totaling up to 7354 and 1901, respectively. Concurrently, fissures inside the specimen increased continuously, accompanied by more complex dip directions and angles of interfacial fractures. The final scattering angles of fractures at the upper interface were 86 °, 119 °, 124 °, and 137 °, while that of fractures at the lower interface was 116 °. During loading, the specimen exhibited a composite fracturing pattern characterized by inverted V-shaped and clustered fractures. The fractures were primarily concentrated in the TDC, in which fractures represented 78.5% of the total. The fracture volume and ratio decreased initially, followed by a slow increase, a rapid increased, and a slow increase sequentially. The length of the dominant fracture rose from 44.7 mm to 99.4 mm. The fracture propagation rate displayed a trend of decreasing first, then increased, and decreased finally. Using the mesoscopic damage mechanics model and the two-parameter Weibull distribution, this study constructed a model for fracture propagation characterization of the TDC-bearing combination specimen and developed a flow chart for discriminating the formation path of the dominant fracture in the specimen during loading. The rationality of the discriminant process was verified using the Matlab software, yielding relative errors ranging from 1.54 % to 4.21 %. Finally, this study revealed the dynamic evolutionary patterns of fractures in the specimen during loading. This study provides a theoretical basis for investigating factors inducing dynamic hazards in coals under the mining disturbance of coal seam combinations.